Occupational radiation dose and protection to the eye lens for interventional cardiology operators. (June 2022) - Lian, Meng-En; Wu, Guan-Yi; Chao, Min-Fang; Wang, Chong-Sheng; Miao, Hsiao-Chien; Tsai, Ming-Sung; Hsieh, Mu-Yang; Chen, Yeh-Peng; Chu, Chun-Yuan; Chang, Szu-Li; Tsai, Hui-Yu
Abstract: Objectives: Interventional professionals tend to receive extended radiation exposure given the complexity and machine settings of procedures in interventional cardiology departments, resulting in a high eye lens dose. This study developed a method for estimating the occupational radiation dose to the eye lens based on the personal dose equivalent to the skin at 0.07-mm depth [ H p (0.07)] obtained using an over-apron dose badge, investigated whether glasses with lateral shielding but a thin Pb-equivalent material could adequately protect the eye lens from radiation in clinical situations, and identified factors affecting the occupational radiation dose to the eye lens. Methods: The occupational radiation dose was prospectively measured using dosimeters near the eye and over the lead apron at the collar level in 26 interventional professionals performing 444 procedures in interventional cardiology departments. Type A (0.07-mm front and lateral Pb equivalence) and type B (0.5-mm front Pb equivalence and 0.25-mm lateral Pb equivalence) glasses were worn by the operators during operation to protect the eye lens. Results: The median personal dose equivalent to the eye lens at 3-mm depth [ H p (3)/dose area product (DAP)] of the primary operator was the highest (7.6 μSv/Gycm 2 ) for upper limb percutaneous transluminal angioplasty among all examined procedures. The secondary operator's median H p (3)/DAP values ranged from 17% to 41% of that of the primary operator. The median H p (3)/DAP values did not significantly differ between the primary operators wearing type A glasses and those wearing type B glasses for percutaneous coronary intervention or diagnostic cardiology studies (all p  > 0.05). The Pearson correlation test results revealed significant positive correlations between the H p (3) and H p (0.07). The estimated annual H p (3) values ranged from 3.3 ± 0.6 to 62.4 ± 8.3 mSv and from 6.0 to 8.0 ± 4.6 mSv for the cardiologists and radiographers, respectively. Conclusions: The H p (3) value can be estimated from the H p (0.07) value obtained using an over-apron dose badge at the collar level. Glasses with 0.07-mm front and lateral Pb equivalence provide satisfactory radiation protection to the eye lens. Regularly using appropriate radiation-protective lead glasses, adopting small angles for left anterior oblique projections, and undertaking moderate workloads are highly recommended to prevent cardiologists from receiving excessive radiation doses to the eye lens. Highlights: Lead glasses with proper design and lighter weight were recommended. Factors affecting the H p (3) values were identified. A model for estimating H p (3) from the H p (0.07) value was developed. Strategies of radiation protection to the eye lens were proposed.